The Pacific challenge: Development trends in the 21st century - Michael Waibel; Werner Kreisel (Universitätsverlag Göttingen, 2005)
The enormous leaps of growth and development experienced by Eastern and Southeast Asian states since the 1960s on account of their astonishing industrial development have led to concerns that a resulting global economic and political shift might favour the Pacific region at the expense of the "Atlantic region". A "Pacific century" was proclaimed, in which it was predicted that Asian-Pacific countries would outpace the traditional leading powers of the West. A more careful look quickly reveals that this view is too simplistic. From the point of view of various disciplines and covering different nations like China, Vietnam, Indonesia, Singapore, the Philippines and Papua New Guinea the authors of this publication pursue the question whether the 21st century can already be labelled the "Pacific Century". This was also the title of the interdisciplinary series of lectures held at the University of Göttingen/Germany in the winter semester 2003/2004. This series of lectures was jointly organized by the Department of Geography, the University of Göttingen and the Association of Pacific Studies e.V. (APSA). This 10th volume of the publication series "Pazifik Forum" contains contributions by W. Kreisel, M. Taube & Ka-Wai Yiu, M. Waibel, A. Croissant, B. Dahm, H. Schneider, R. Seib and R. Jordan.
urn:nbn:de:gbv:7-isbn-3-938616-10-5-6
Keywords: 330; development aid: southeast asia; pacific; Entwicklung; Asiatisch-pazifischer Raum